시설농자재 산업의 발전방안 연구 - 권오복 (한국농촌경제연구원, 2009)
The Korean agricultural equipment material market is stagnant mainly due to the slowdown of greenhouse agriculture. Many firms are facing difficulties in surviving in the severe market competition. On December 2008, Korean government established "the Comprehensive Development Plan for Agricultural Material Industry including agricultural equipment material industry. However the action plan for agricultural equipment material industry was not finalized because of the lack of necessary information. The follow-up measures are needed to be made based on the exact information on the industry. This study was carried out to suggest the development strategies and policy measurers for the agricultural equipment material industry. The study encompasses the frame materials, covering, materials for controlling greenhouse environment, and materials for supplying water and nutrition. The market size of Korean agricultural equipment material industry in 2008 was estimated to be about 0.95 billion US dollars. Among agricultural equipment materials, the market size of frame materials is the largest accounting for 47.6 percent of the total agricultural equipment material market followed by covering(31.3 percent), materials for supplying water and nutrition(7.3 percent), and materials for controlling greenhouse environment(7.0 percent). The market structure of most of agricultural equipment materials is characterized as oligopoly existing several, but not many firms competing each other. In the case of some industries only one company dominates the market. It is surveyed that most of greenhouse farms purchase agricultural equipment materials in the private agricultural input shop. In case of plastic film and pipe for greenhouse, the national agricultural cooperation federation(NACF) supplies about seventy percent of the supply to greenhouse farms. The NACF makes a contract of supplying plastic film and pipe with firms. Accordingly, it has dominant market power over the firms. In 2008, the export of major agricultural equipment materials is approximately 2.5 billion US dollars, an annual increase of 9.1 percent since 2000. The export of coverings including the PET(polyethylen terephthalate) is the most among agricultural equipment materials followed by the materials for controlling greenhouse environment. The major export markets of coverings are Japan, the United States, China, and Italy. In the same year the import of major agricultural equipment material materials is about 1.5 billion US dollars. The import of coverings is the most followed by the materials for controlling greenhouse environment. The major import markets of coverings are Japan, China, Thailand, Indonesia, and Taiwan. The non-woven curtain and aluminium screen are imported from China, the United States, Japan, and Netherlands. In the Horti Fair held on October 13-16, the Amsterdam, Netherlands ten Korean firms made contract of about ten million US dollars with foreign buyers. During the Fair, many buyers from other countries including hosting country, the Netherlands were interested in the high quality of Korean agricultural equipment materials. It was observed that a lot of Korean agricultural equipment materials could be exported to other countries if they had high quality of agricultural equipment materials and promoted export market successfully. According to the survey result of greenhouse farms, management cost including heat and light expenses is the most difficulty facing the greenhouse farms followed by short of manpower and dark market prospect. Many greenhouse farms plan to reduce the size of greenhouse due to these problems. It is also surveyed that many greenhouse farms think the price of agricultural equipment materials too expensive. Many greenhouse farms also use imported agricultural equipment materials because of high quality of foreign agricultural equipment materials. They replied that they continued to use imported agricultural equipment materials if the quality and price are superior to domestic products. It is estimated that the area of greenhouse would increase continuously reaching 59,069 ha in 2020. Due to the increase of the area of greenhouse, the market size of agricultural equipment materials would be also expanded during the period of estimation, 2010~2020. The market size of agricultural equipment materials is estimated to be 1.3 billion US dollars in 2020, annual increase of 3.1 percent. The study suggested five development strategies; avoidance of severe competition in the market through the mergers and acquisitions(M&A), co-buying materials, improving quality of the agricultural equipment materials, developing and supplying suitable for greenhouse demand such as energy saving materials and automation equipment, promoting export market. As for government two policy measures are recommended. First, the government should strengthen the demand base for agricultural equipment material industry by nurturing greenhouse agriculture, assisting farms repairing the greenhouse, and supplying energy saving agricultural equipment materials. Second, the government needs to improve the competitiveness of the industry by adjusting the structure of the industry, R&D for agricultural equipment materials, assisting agricultural equipment material export, and producing necessary statistical data on the industry of agricultural equipment materials.
Keywords: 농자재; 시설농업; 원예산업